ESSENTIAL OILS AS POTENTIAL ECOLOGICAL WOOD PRESERVATIVES – A PRELIMINARY TEST ON THYME ESSENTIAL OIL (Innovation in Woodworking Industry and Engineering design, 2026)
The paper refers to a laboratory test, designed to allow a quick and reliable evaluation of the potential biocidal effect of essential oils. These are intended to be used as ecological wood preservatives with antifungal properties, for various applications including furniture conservation. The screening tests employed thyme (Thymus vulgaris) essential oil at 3 different concentrations and two types of fungi, one white rot Trametes versicolor and one brown rot Postia placenta. Based on these tests, thyme (Thymus vulgaris)essential oil has proven to be a potential active fungicide against the brown and white rot fungi, in a wide range of concentrations.